Severe Asthma Toward Personalized Patient Management (Springer Singapore, 2018)
This book presents state of the art knowledge on severe asthma with the aim of providing readers with a clear understanding of, first, the heterogeneity of the condition and of patients' symptom profiles and responses to therapy and, second, the future implications of this heterogeneity for individualized patient care. After an opening section that offers an overview of severe asthma, including its clinical significance, the pathogenesis, available diagnostic approaches, and treatment options are described in detail. The sections on diagnosis and treatment cover the role of biomarkers, the use of radiologic diagnostic modalities, and both pharmacologic and non-pharmacologic therapies, including emerging options that will address hitherto unmet needs of patients. The outcomes of cutting-edge preclinical and clinical research are carefully documented and numerous useful tips provided on patient management. The inclusion of many informative schematic figures will assist readers in grasping the contents easily. The book will be of high value for medical students, researchers, general physicians, specialists, and paramedical staff.